OP0069 Varicella Vaccination in Patients with Paediatric Rheumatic Diseases Receiving Immunosuppression: Proposal of a Pre-Vaccination Check List to Ensure Safety. (9th June 2015) - Speth, F.; Hinze, C.; Loeber, S.; Haas, J.-P.
Abstract : Background: Varicella zoster virus (VZV) infection is a serious preventable infection in patients receiving immunosuppression. The safety of varicella vacination (VV) in patients with paediatric rheumatic disease (PRD) while receiving immunosuppression (IS) has been debated. Objectives: To evaluate the safety of 1st and/or 2nd dose varicella vaccine (VV) in patients (pts) with PRDs receiving IS after passing a pre-vaccination check list of immunologic criteria. Methods: In this single centre study, 21 VZV-susceptible pts with clinically inactive PRDs, including different categories of juvenile idiopathic arthritis and connective tissue diseases between the ages of 2–18 years on low-intensity IS (LIIS) (methotrexate [MTX] ≤15mg/m 2 /week and/or prednisolone <10mg/day) or high-intensity IS (HIIS) (MTX>15mg/m 2 /week, leflunomide, mycophenolate mofetil [MMF], etanercept, tocilizumab, anakinra, abatacept, or a combination thereof) were included in this study. Prior to vaccination, pts were screened according to an immunologic checklist with predefined cut-offs (for pts on LIIS: WBC>3000/μl, ALC>1200/μl, IgG>500mg/dl, IgM>0, Tetanus toxin-IgG >0, 10IU/ml; in addition, for pts on HIIS: CD4 >200/μl [if>5 yrs] or CD4 >500/μl [if 1-5 yrs] and positive T cell reactivity to mitogen or antigen, e.g. via TB-EliSpot positive control. Pts meeting these safety criteria received either a 1st and/or 2nd dose of VV without suspension of IS. VZV-IgG levels were measured before applying VV and after each dose. VZV cellular mediated immunity (CMI) was measured after VV. Potential side effects and PRD flares were monitored. Results: Out of 9 pts receiving LIIS and 12 pts receiving HIIS none failed the immunologic checklist. 8 pts (2 LIIS, 6 HIIS) had already received their 1 dose of VV prior to this study and received a 2nd/booster dose of VV only. 13 pts (7 LIIS, 6 HIIS) received their 1st dose of VV within the study and 7 of these 13 pts received a 2nd dose of VV. 11/13 pts demonstrated VZV-IgG levels of >150 IU/ml after the 1st dose of VV, and 5/7 pts of those receiving a 2nd dose of VV achieved levels of >500 IU/ml. 1 pt (on MMF) did not achieve protective VZV-IgG levels and 1 pt (on leflunomide and abatacept) did just achieve a VZV-IgG level of exactly 150 IU/ml, despite 2 doses of VV and adequate humoral and cellular immunity. Of those 8 pts receiving a booster dose only, all exceeded VZV-IgG levels of >500 IU/ml by far. There was no difference in either the mean absolute or relative increase (Δ) in VZV-IgG between pts on LIIS vs. HIIS (after 1st dose of VZV Δ341 IU/ml vs. Δ378 IU/ml and 4.7-fold vs. 4.2-fold, respectively; after 2nd dose Δ745 IU/ml vs. Δ1001 IU/ml and 6.9-fold vs. 6.4-fold, respectively). Data on VZV-CMI were pending at the time of abstract submission. There was no evidence of VV-induced varicella or other VV-associated complications. None of the pts developed a PRD flare and no change in the IS regimen was required in any pt during a minimum follow-up of 4 wks. 7 pts had transient arthralgias of unclear association with VV administration. Conclusions: After meeting easy-to-obtain immunologic criteria, the VV could safely be applied to a diverse cohort of pts with clinically inactive PID on IS with excellent response in the majority of pts. Acknowledgements: Supported by a grant from "Verein Hilfe für das rheumakranke Kind". Disclosure of Interest: None declared